Placental mechanism of prenatal nicotine exposure-reduced blood cholesterol levels in female fetal rats. (15th October 2018) - Zhang, Guohui; Zhou, Jin; Huang, Wen; Yu, Luting; Zhang, Yuanzhen; Wang, Hui
Highlights: Prenatal nicotine exposure(PNE)induces low cholesterol levels in female fetal blood. Reduced placental cholesterol transport mediates PNE-induced low cholesterol levels in female fetal blood. nAChR-LXR signaling is involved in PNE-reduced placental cholesterol transport. Abstract: Clinical studies showed that intrauterine growth retardation (IUGR) neonatus had lower cholesterol concentrations in cord blood, which might be associated with increased risk of metabolic syndrome and cardiovascular diseases in adulthood. We previously observed lower blood cholesterol levels in prenatal nicotine exposure (PNE)-induced IUGR fetal rats, and this study aimed to elucidate the placental mechanism. Pregnant Wistar rats were subcutaneously injected with nicotine (2.0 mg/kg⋅d) on gestational day 9–20. In vivo, PNE increased levels of total cholesterol (TCH), high-density lipoprotein-cholesterol (HDL-C) and low-density lipoprotein-cholesterol (LDL-C) in maternal serum, while decreased levels of TCH and LDL-C in female fetal serum. Meanwhile, the expression of scavenger receptor class B type 1 (SR-B1), ATP-binding cassette transporter A1 (ABCA1) and ATP-binding cassette transporter G1 (ABCG1) were decreased, and the expression of liver X receptor (LXR) α and β were also decreased in female placentas. In vitro, nicotine (0.1–10 μM) reduced the expression of LXRα, LXRβ, SR-B1, ABCA1 and ABCG1 in a concentration dependent manner, which could be annulled by nAChR antagonist and LXR agonist. Taken together, nicotine could inhibit the expression of SR-B1, ABCA1 and ABCG1 via nAChR and LXR α/β in female placentas, finally leading to reduced blood cholesterol levels in fetal rats.